Political language and fake news: Some considerations from the 2019 election in Indonesia. Issue 143 (2nd January 2021) - Duile, Timo; Tamma, Sukri
ABSTRACT: This article outlines political symbolism and language in the 2019 election in Indonesia and aims to situate fake news narratives within them. By analysing official election campaign posters ( spanduk ), it is argued that Islam and nationalism are the only ideological references and are applied by both camps, leaving no room for other forms of ideological contestation. The article suggests understanding this phenomenon as a hegemonic, Gramscian 'common sense' which creates a notion of unity of the nation. This unity, however, is disturbed by hoaxes as in fake news. But instead of referring to hoaxes only as a threat to Indonesian politics, we argue that hoaxes are an integral part of the 'common sense'. Hoaxes are a means to make the ideological framework of Islam and nationalism accessible for the popular masses, applying a kasar (rough) approach, contradicting the halus (soft) language of the political elite. They are also inevitably a means to create the impression that the camps are distinct. As hoaxes refer to the constitutive outside of the nationalism-Islam complex (as Islamists suggest that Jokowi has ties to the outlawed Communist Party or that Prabowo aims to establish an Islamic state, for instance), they serve the function of maintaining the ideological order in post-New Order Indonesia.